An Exploratory Study on the Characteristics of Korean Senior Fashion Influencer Using Netnography Analysis - Park, Sunyang (International Journal of Costume and Fashion, 2024)
This study employs a qualitative research approach to examine Korean senior influencers who focus primarily on fashion content. While global research on senior fashion influencers is thriving, there is a notable lack of domestic literature. To address this gap, the researcher conducted an exploratory analysis of Korean fashion senior influencers using a netnographic research method to observe and analyze online data for significant themes. The study focused on the top 10 most-viewed posts, resulting in a visual and textual analysis of a total of 90 posts. The findings reveal distinctive characteristics of domestic senior fashion influencers: originality, attractiveness, informativeness, and entertainment. These traits set them apart from other senior influencers and individuals in different age groups, as they embrace trendy fashion styles and continuously explore new looks (originality), invest considerable effort in maintaining physical attractiveness and creating appealing content (attractiveness), provide valuable information on health, beauty, and fashion (informativeness), and deliver engaging content through creative editing (entertainment). Given the limited research on Korean senior influencers to date, this study contributes to raising academic awareness and encouraging further investigation in this area. KCI Citation Count: 0